Pengembangan Buku Saku Digital Berbasis STEM Terhadap Pemahaman Konsep Matematis - Komarudin Komarudin; Inne Dwi Utari; Farida Farida; Suherman Suherman (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2021)
This study aims to develop and determine the feasibility, response of students, and the effectiveness of STEM-based digital pocket book on students' ability to understand mathematical concepts in algebraic and PLSV forms of material. The subjects of this study were students of class VII SMP/MTs. This type of research is Research and Development (RD) using the ADDIE model which includes 5 stages, namely: Analysis, Design, Development, Implementation, and Evaluation. The data collection instrument in this study was a validation questionnaire given to expert validators and a student response questionnaire. The results of the validation data analysis from the material expert and media expert were respectively found to have a mean value of 3.87 and 3.54 so that the digital pocket book was declared in the suitable category. The results of the analysis of the attractiveness response test data obtained a mean final score of 3.43 for small group trials and 3.6 for large group trials so that the digital pocket book developed was very interesting to use. The test of the effectiveness of STEM-based digital pocket books on students' ability to understand mathematical concepts could not be carried out because of limitations due to the COVID-19 pandemic which also had an impact on the learning process in schools. Therefore, this research and development is only carried out until the development stage.